Relationship between person environment fit and career Development among employees at Institut Kemahiran Belia Negara (IKBN) Kedah - Noorhidayah, Zakaria (2019)
This study was conducted to identify the relationship between Person Environment Fit and Career Development among employees at IKBN in Kedah. Person Environment fit was measured using five dimensions, namely Person Job fit, Person Group fit, Person Supervisor fit, Person Vocation fit and Person Organization fit. This study used cluster sampling technique, and sample selection was among staff at both IKBNs from three departments, which are Administration, Students Affair Department and Training Department. This study used quantitative technique and questionnaire was used as an instrument for data collection. To analysed the data, total 152 questionnaires were collected and further analysed using Statistical Packages for Social Science (SPSS) version 22.0. The data was analyse using descriptive analysis, factor analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. Five (5) hypotheses were developed in this study. From the data analysed results, the study found all five dimensions namely Person Job fit, Person Group fit, Person Supervisor fit, Person Vocation fit and Person Organization fit have significant and positive relationship with career development. It shows that all five hypotheses were accepted. Based on this finding, IKBN Kedah need to focus on upgrading the all Person Environment fit dimensions to motivated employees to participate in their career development activities.